Effect of quercetin and prima-1MET (P53 activator) combination therapy on P53 mutant type human colon cancer cells (COLO-320) - CHANDRA SEKHAR PASULA; DR. SAVITHIRI SHIVAKUMAR; YASODHA LAKSHMI T; RAJA RATNA REDDY Y; DR. S. RAMAMOORTHY (International Journal of Pharma and Bio Sciences, 2019)
Tumor suppressor p53 (TP53) is the most frequently mutated gene in many of human cancers including colorectal cancer. Colorectal cancer (CRC) is the third most common cancer world wide and is the main cause of cancer linked deaths in western countries. The incidence of CRC cases were increasing due to change in lifestyle and diet factors. Mutation in p53 is one of the major reasons for deregulation of normal cell cycle process and apoptosis. Tumors with p53 mutations are more resistant to regular cancer therapies. Hence, Combination therapies got more importance in cancer treatment. In this study, p53 mutant type cultured colon cancer cells (COLO-320) were treated with quercetin and PRIMA-1MET(p53 activator) combinations and their effects were estimated in cell viability, colony formation assays, cell cycle arrest by Flow cytometry and the rate of apoptosis by fluorescent microscopic examination of apoptotic cells - DAPI staining method, estimation of caspase-3, -9 activities, p53, Pro and anti apoptotic Bcl-2 family proteins. Results showed significant decrease in COLO-320 cell viability, clonogenicity with G2 phase cell cycle arrest. Combination treatment induced apoptosis with significant increased caspase-3, -9 activity and also significant effect on normalization of pro and anti-apoptotic Bcl-2 family proteins with increased p53 activity in apoptosis. Over all results confirmed that quercetin+PRIMA-1MET combinations (both at same time treatment) are more effective against COLO-320 cell growth than individual treatments. Based on these findings quercetin and PRIMA-1MET combinations induced p53 mediated apoptosis is the reason for anticancer activity in COLO-320 colon cancer cells and these findings will become a significant rationale for combination target therapies in colorectal cancer treatment.